Skin-interfaced electronics: A promising and intelligent paradigm for personalized healthcare. (May 2023) - Zhu, Yangzhi; Li, Jinghang; Kim, Jinjoo; Li, Shaopei; Zhao, Yichao; Bahari, Jamal; Eliahoo, Payam; Li, Guanghui; Kawakita, Satoru; Haghniaz, Reihaneh; Gao, Xiaoxiang; Falcone, Natashya; et al.
Abstract: Skin-interfaced electronics (skintronics) have received considerable attention due to their thinness, skin-like mechanical softness, excellent conformability, and multifunctional integration. Current advancements in skintronics have enabled health monitoring and digital medicine. Particularly, skintronics offer a personalized platform for early-stage disease diagnosis and treatment. In this comprehensive review, we discuss (1) the state-of-the-art skintronic devices, (2) material selections and platform considerations of future skintronics toward intelligent healthcare, (3) device fabrication and system integrations of skintronics, (4) an overview of the skintronic platform for personalized healthcare applications, including biosensing as well as wound healing, sleep monitoring, the assessment of SARS-CoV-2, and the augmented reality-/virtual reality-enhanced human-machine interfaces, and (5) current challenges and future opportunities of skintronics and their potentials in clinical translation and commercialization. The field of skintronics will not only minimize physical and physiological mismatches with the skin but also shift the paradigm in intelligent and personalized healthcare and offer unprecedented promise to revolutionize conventional medical practices. Graphical abstract: Image 1